Exploring the associations between spiritual well-being, burden, and quality of life in family caregivers of cancer patients. Issue 3 (11th May 2018) - Spatuzzi, Roberta; Giulietti, Maria Velia; Ricciuti, Marcello; Merico, Fabiana; Fabbietti, Paolo; Raucci, Letizia; Bilancia, Domenico; Cormio, Claudia; Vespa, Anna
Abstract: Objective: The spiritual dimension is important in the process of coping with stress and may be of special relevance for those caring for cancer patients in the various phases of caregivership, although current attention is most prevalent at the end of life. This study explores the associations among spiritual well-being (SWB), caregiver burden, and quality of life (QoL) in family caregivers of patients with cancer during the course of the disease. Method: This is a cross-sectional study. All participants ( n = 199) underwent the following self-report questionnaires: the SWB-Index, the Medical Outcomes Study Short Form, and the Caregiver Burden Inventory (CBI). SWB scores were dichotomized at a cutoff corresponding to the 75th percentile. Statistical analyses were made using the Student t or by chi-square test to compare high and low SWB groups. Result: The high SWB group reported significantly better Medical Outcomes Study Short Form scores in bodily pain ( p = 0.035), vitality ( p < 0.001), social activities ( p = 0.001), mental health ( p < 0.001), and in standardized mental component subscales ( p < 0.001) than the low SWB group. No significant differences were detected between the two SWB groups in physical activity, physical role, general health, emotional status, and standardized physical component scale. The high SWB group also had better CBI scores in the physical ( p = 0.049) and developmental burden ( p = 0.053) subscales. There were no significant differences in the other CBI scores (overall and sections). Significance of results: This study points out that high SWB caregivers have a more positive QoL and burden. Knowledge of these associations calls for more attention on the part of healthcare professionals toward spiritual resources among family cancer caregivers from the moment of diagnosis and across the entire cancer trajectory.